Libertad e igualdad en la contratación. La afectación de derechos fundamentales - Ruiz Rico Ruiz, José Manuel (UMA Editorial (Universidad de Málaga), 2026)
Inaugural lecture given by Professor D. José Manuel Ruiz-Rico Ruiz on the occasion of the opening of the 2023-2024 academic year at the University of Malaga.